2013
DOI: 10.1189/jlb.0313144
|View full text |Cite
|
Sign up to set email alerts
|

Distinct development and functions of resident and recruited liver Kupffer cells/macrophages

Abstract: Although mouse liver F4/80(+) Kupffer cells consist of cytokine-producing CD11b(+) cells and phagocytic CD68(+) cells, an undefined CD11b(-) CD68(-) subset (30%) also exists. We herein demonstrate a more fundamental classification by adding CD32 (FcγRII), which covers most liver F4/80(+) cells and the distinct functions of them. Among the F4/80(+) cells, 50%, 40%, and 30% of cells were CD32(+), CD68(+), and CD11b(+), respectively, and one-half of the CD68(+) cells coexpressed CD32. CD68(+) and CD32(+) cells, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
142
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(146 citation statements)
references
References 42 publications
4
142
0
Order By: Relevance
“…12 a). This result was consistent with previous reports [9,10,18] . Despite the depletion of the CD68 + subset in the liver, LPS-primed mice still showed strong resistance to a lethal bacterial challenge ( Fig.…”
Section: Subset Of Liver F4/80supporting
confidence: 83%
See 3 more Smart Citations
“…12 a). This result was consistent with previous reports [9,10,18] . Despite the depletion of the CD68 + subset in the liver, LPS-primed mice still showed strong resistance to a lethal bacterial challenge ( Fig.…”
Section: Subset Of Liver F4/80supporting
confidence: 83%
“…The former is also CD11b low , while the latter are CD11b high . Interestingly, Davies et al [22] + subset with strong phagocytic activity (tissue resident) and a CD11b + subset with potent proinflammatory cytokine-producing capability (bone marrow derived) [9,10] . Consistent with the report of Davies et al [22] ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed flow cytometric and immunohistochemical studies also revealed that the CD68 + cells are large and spindle-shaped, while the CD11b + cells are small and round or oval-shaped (Ikarashi et al, 2013). While large macrophages are more phagocytic and generate increased quantities of lysosomal enzymes, the smaller macrophages release more reactive oxygen species, and appear to be more susceptible to`M1`-type activation and cytokine production.…”
Section: Discussionmentioning
confidence: 97%